PENGARUH EFEKTIVITAS IKLAN DI TELEVISI TERHADAP KEPUTUSAN PEMBELIAN MINUMAN RINGAN BAGI MAHASISWA STIE SEMARANG - Dwi Prawani Sri Redjeki; Jefri Heridiansyah (STIE Pelita Nusantara Semarang, 2016)
Selection of a media campaign with television ads can doing as appropriate to the means of communication that could form the name for a product by displaying sound, color and movement. Product advertising messages are expected to show the superiority of the product, persuading and directing consumers in the purchase action in accordance with company objectives in order to increase sales and profits. Promotion with advertising on television coupled with the frequency of how often your ads and ad duration may be longer shown on television, it was ensured the success of the product concerned for sale to the public is increasingly getting bigger.The population used is STIE SEMARANG student who had done or buy a soft drink after seeing the ads on soft drinks. Data obtained from 60 students STIE SEMARANG both management or accounting courses sample. The results of hypothesis testing either partially or simultaneously shows the results of analysis that they all support the hypothesis H.1 until H.4 proposed that the effectiveness of advertising through television media in terms of advertising forms (X1), the content of the ad (X2) and the frequency or duration of advertisements ( X3) partially and simultaneously significant effect on purchasing decisions (Y) soft drinks for students STIE SEMARANG. Results of the analysis showed that the purchasing decisions of soft drinks to students STIE SEMARANG variable forms of advertising (X1) as the factors that most influence